10 jaar cultuurprijs K.U. Leuven 1992-2002. - Beirens, Maarten; Caeyers, Jan; Châtel, Guy; De Baets, Isabelle; Derycke, Luc; Jacobs, Steven; Janssens, Marcel; Laermans, Rudi; Pas, Johan; Snauwaert, Dirk; Van Kerkhoven, Marianne; Verpoest, Luc, 1945-; et al. (Leuven : K.U. Leuven Cultuurcommissie, 2002)
Caeyers, Jan ; Deleu, Luc ; De Keyser, Raoul ; Van Kerkhoven, Marianne ; Champ d'Action ; Janssens, Ann Veronica ; Tuerlinckx, Joëlle ; Tuymans, Luc ; Brewaeys, Luc ; Stuart, Meg ; Damaged Goods ; Robbrecht, Paul ; Daem, Hilde ; Braeckman, Dirk
Voorstelling Laureaten (beperkte biografie) p. 86-94
Nederlands
boek